Świat roślin w opowiadaniach Ludzie stamtąd Marii Dąbrowskiej - Kobylińska, Józefa; Horyń, Ewa (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2015)
The article presents 89 names which belong to plant lexis. The linguistic material was excerpted from short stories Ludzie stamtąd (People from There) by Maria Dąbrowska. The terminology which is discussed belongs to 10 lexical-semantic areas, namely: 1. Wild and cultivated trees; 2. Wild or cultivated bushes; 3. Wild and cultivated flowers; 4. Herbaceous plants; 5. Lichens; 6. Grasses; 7. Grains; 8. Vegetables; 9. Plant locations; 10. Plant fruits. These names serve a few important functions in the presented works: they take part in the creation of the presented world, they accompany the characters’ moods and emotions, they have a decorative function, and they also play a therapeutic (thus practical) role.